UJI AKTIVITAS SENYAWA ANTIOKSIDAN DARI EKSTRAK DAUN TIIN (Ficus Carica Linn) DENGAN PELARUT AIR, METANOL DAN CAMPURAN METANOL-AIR - EVA AGUSTINA (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2017)
Antioxidants can ward off free radicals in the body to resist oxidative damage caused by free radicals. The aim of this research is to know the influence of water solvent, methanol and methanol-water mixture to antioxidant activity. The extraction is done by maceration method. The extraction results in the phytochemical test and functional group analysis to determine the compounds contained in Pig leaf extract. Further testing of antioxidant activity with DPPH method. Pig leaf extract with methanol solvent has antioxidant activity with IC50 3,3005 μg / ml value, Pig leaf extract with water solvent has antioxidant activity 3,6976 μg / ml and Pig leaf extract with methanol solvent: water has antioxidant activity 13,6140 μg / ml. The IC50 <50 μg / ml value indicates that the Pig leaf extract with some solvents has potent antioxidant potential. Pig leaf extract with methanol solvent has the best antioxidant activity with IC50 3,3005 μg / ml value because according to phytochemical test and functional group analysis that methanol solvent is able to extract more active compound such as flavonoid, Triterpenoid and Sterol, Alkaloid and Saponin followed by Pig leaf extract with water solvent and methanol mixture: water.